Antecedents of unethical behaviour intention among working young adults - Tengku Intan Nabilah, Tenku Sulaiman; Fatimah, Mahmud; Hasnah, Haron (GBMR, 2025)
Purpose: This study aims to investigate the relationship between attitude (greed), subjective norms (parental influence, peer influence), and perceived behavioural control (financial pressure, capability) towards intention to perform unethical behaviour amongst working young adults in the Malaysian local authority. Design/methodology/approach: A self-completed questionnaire was designed and distributed to working young adults in Malaysian local authorities between the ages of 21 and 40 years old to obtain the research data. Data was gathered from 208 eligible respondents and was analyzed using descriptive statistics and the PLS-SEM technique to test the proposed hypotheses. Findings: Results from the analysis revealed that parental influences and peer influences have a significant relationship towards intention to perform unethical behaviour. The present study provides valuable insights for working young adults and Malaysian Local Authorities, offering practical implications to address the factors influencing unethical behaviour intention. Research limitations/Implications: The research design of this study only focuses on quantitative data, where the quantitative results can lead to general findings, whereas this study lacks in-depth findings. Practical implications: The findings of this study will highlight the role of working young adults as future leaders. Consequently, it is important for working young adults to have the right attitude and avoid unethical behaviour by educating them the awareness on the intention to perform unethical behaviour. Originality/value: This study developed a common ethical scenario to measure unethical behaviour amongst working young adults based on the definition of unethical behaviour applicable in Malaysia. The framework was underpinned by the integration of the theory of planned behaviour (TPB) and fraud diamond theory (FDT).